Students’ perspectives on application of AI-powered technology in learning English pronunciation: a case of reading progress - Thuan, Pham Duc; Hong Hanh, Nguyen Thi (Institute of Advanced Engineering and Science, 2025)
Artificial intelligence (AI) is increasingly dominating several aspects of human existence, including the realm of English pronunciation instruction. Reading progress is an AI-driven application created by Microsoft in Microsoft Teams to aid language learners in honing their pronunciation skills. Nevertheless, there is a scarcity of research accessible about this use. The objective of this research is to examine students’ assessments of the tool’s effectiveness in facilitating the acquisition of English pronunciation. This study used a questionnaire consisting of five questions, created using Google Forms, to collect data from 123 students who are enrolled in different English classes at a university located in northern Vietnam. The focus of the research is on the students’ pronunciation skills. The study results suggest that learners have a favorable opinion of and see reading progress as a valuable tool for honing their pronunciation skills. This outcome enhances the body of research on the implementation of reading progress in the context of teaching English pronunciation in Vietnam and globally. Thus, learners and English instructors may consult and implement it in order to enhance the efficiency of learning and teaching.